Pengaruh Bagian Rebung dan Perlakuan Pendahuluan Terhadap Karakteristik Tepung dari Rebung Bambu Tabah (Gigantochloa nigrociliata BUSE – KURZ) - Howard Patty, Richard; Semadi Antara, Nyoman; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2014)
The objective of this research was to know the effect of bamboo shoot parts and pre-treatment process on nutrition content and the color of flour from Tabah bamboo shoot. The laboratory scale experiments were designed by using randomized block design. Three parts of bamboo shoot (tip, middle, and lower parts) were processed in order produce to bamboo shoot flour by using two different pre-treatment processes, namely blanching and pickling process. The results of experiment show that interaction of the parts of bamboo shoot and pre-treatments used to process bamboo shoot to become flour affected the nutritions content of the bamboo shoot flour. Lower part of bamboo shoot and blanching pre-treatment process produce the best characteristics of bamboo shoot flour. The flour had the highest content of crude fiber (25.82%db) with the content of starch, protein and ash were 8.83%db, 23.97%db and 12.26%db, respectively. The flour showed bright color with the L value about 44.47 and the respective value of a and b were -12.76 and 49.36. The rendement of the process was 4.18%wb.
Keywords: 24